Penerapan Algoritma Greedy Dalam Pencarian Jalur Terpendek Pada Instansi-Instasi Penting Di Kota Argamakmur Kabupaten Bengkulu Utara - Darnita, Yulia; Toyib, Rozali (UNIVED Press, 2019)
Searching for important agencies in the city of Argamakmur is an important thing for people from outside the area to do in moving either non-permanent (temporary) or permanent (permanent) in an area, thus the difficulty in accessing distance and time is one of the factors. which needs to be considered in order to obtain information on where the positions of the agencies are precisely and accurately. When searching, the Greedy Algorithm works by looking for the smallest weight point by calculating the route passed and the Greedy Algorithm calculates the weight depending on the weight of the stage that has been passed and the weight of the stage itself. Based on the results of testing the system created: Local Government travel time is 10 minutes on the shortest route to Gunung Alam, Capil travel time is 10 minutes on the shortest route to Karang Suci, Porles travel time is 8 minutes on the shortest route on a roundabout, Fire Department travel time is 10 minutes on the shortest route on the square, PLN on time The shortest route takes 10 minutes to the main square, the Regional General Hospital (RSUD) takes 6 minutes to the shortest route to Rama Agung. The shortest route may take longer because of crowds and population density. To run this system, an adequate internet network is needed